Toward A Rupture in the Sensus Communis: On Sound Studies and the Politics of Knowledge Production - Kheshti, Roshanak (Current Musicology, 2017)
In Christine Sun Kim,a film by Todd Selby, we follow the performance artist from her apartment to a busy street corner in New York’s Chinatown where she records a soundscape, jots down some notes and ruminates on the project to which the film gives us a behind-the-scenes view.1 Cut to a scene of loud rustling and various shimmering and colorfully dusty ma-terials dancing on a speaker cone as Kim blows into a microphone dialed up to full volume. The spectator watches and listens from the sidelines of her studio as Kim experiments with the audio recordings she (presumably) made earlier, channeling them to numerous speakers that have various materials taped to or placed on their cones, vibrating wildly, animating sound anew.